(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Nurses played dual roles during the First World War. On the one hand, they functioned as witnesses to men’s war, acting as a link between home and front, for example by writing letters on behalf of their patients to families and loved ones at home. On the other hand, they were active participants in the conflict, offering vital medical care, and operating closer to the front than the majority of their sex, which sometimes blurred the line between (male) combatant and (female) civilian. The complex relationship between these roles of passive witness and active participant are often expressed in their writings. This article will consider several accounts of nursing, both published and unpublished, produced during and after the war in France and Britain. It will distinguish between different kinds of women involved in nursing work during the First World War in order to reveal the diversity of experience that existed beneath monolithic cultural myths of ‘the nurse’. It will then explore the tensions evident between the roles of witness and participant as they are revealed in nurses’ accounts. Nurses express a desire both to act as a channel through which male combatant experience can be expressed, and to write into history the voice of a mobilised woman on ‘active service’.